Determinantes de carreiras políticas no Brasil, na Argentina e no Uruguai : uma abordagem comparativa entre deputadas e deputados - Danusa Marques (2012)
This research approaches the pathways and the political capital of representatives of Brazilian, Argentinian and Uruguayan Lower Houses, comparing the differences of the elected women and men in each country. It focuses the debate of male and female political profiles, considering gender inequalities and its impact on political careers in different (but nor distant) political systems.